KERAGAMAN KELINCI LAUT (NUDIBRANCHIA) DI PERAIRAN LAUT SULAWESI UTARA - Inri K K Mantiri; Rosita AJ Lintang; Farnis Bineada Boneka; Billy Th. Wagey; Adnan Wantasen; Medy Ompi (JURNAL PESISIR DAN LAUT TROPIS, 2021)
This study aims to 1) identify the species of Nudibranchia in North Sulawesi marine waters, especially in Malalayang waters, Teep waters, Sangihe waters, Bunaken waters, Gangga waters and Lembeh straits, 2) find out species of Nudibranchia that is found in all sites, and 3) find out index community structure of Nudibranchia in all sites.  The result show that there were 11 species of Nudibranchia in Malalayang waters, 27 species in Lembeh Strait, 11 species in Teep waters, 57 species in Bunaken waters, 91 species in Bangka waters, and 20 species in Sangihe waters. Up to now, there were 139 species of Nudibranchia in North Sulawesi marine waters, where Species of Phyllidiella pustulosa, Phyllidia ocellata, Phyllidia varicose, Chromodoris annae, and Glossodoris cincta were found in all study locations. The species of Doriprismatica atromarginata was only found in the Malalayang waters.  A high Index Diversity was found in Bunaken and Bangka waters, and a middle Index Diversity was found in the waters of Lembeh Strait, Teep, and Sangihe. A stable community structure was found for all locations, while a low domination was categorized to all locations. Keywords: Nudibranchia, species, diversity, evenness, domination, and community structure.